The significance of digital citizenship in the well-being of older migrants. (May 2018) - Millard, A.; Baldassar, L.; Wilding, R.
Abstract: Objectives: To understand the increasingly important role of digital citizenship (the ability to participate in society online) in supporting the well-being of ageing migrants. Study design: Participant observation, social network mapping, ethnographic and life-history interviews. Methods: Fifteen in-depth case studies examined the role of online participation in fostering the well-being and care of older migrants in Perth, Western Australia. Participants are members of an 'internet café' that facilitates their shared development of Internet skills. The case studies are derived from ethnographic research conducted between July and October 2016. Results: Older peoples' maintenance of support networks and social engagement, and their access to healthcare services, can be enhanced when they are motivated to increase their digital literacy (the ability to use the Internet for information and communication) through appropriate educational, technological, infrastructure and social support. This support is likely to be more effective when developed through social learning systems that create communities of practice. Improving digital literacy has special implications for the well-being of older migrants because it can enhance their ability to exchange emotional support across distance. Conclusions: Digital literacy for older migrants can dramatically increase their ability to maintain and expand dispersed networks of support. Effective implementation of affordable and age-inclusive information and communication technology (ITC) infrastructure requires integrated support that connects individuals and their homes with social learning systems to ensure that participation continues as mobility declines. As health information and social engagement are increasingly delivered through online platforms, supporting the digital citizenship of older people is becoming an important equity issue. Highlights: Older migrants desire connectivity with local and distant support networks. New media and the Internet facilitate access to support for older migrants. Digital literacy enables older migrants to enjoy greater autonomy and participation. Social learning settings aid development of digital literacy among older migrants. Communities of practice provide holistic support in acquiring digital citizenship.